PENGARUH FINANCIAL DISTRESS, CORPORATE GOVERNANCE DAN KONSERVATISME AKUNTANSI TERHADAP TAX AVOIDANCE - Hendrawan, Agus; Sariyati, Sariyati (Taksasila Edukasi Insani, 2024)
This study aims to see the effect of financial distress, board size, institutional share ownership, and accounting conservatism on tax avoidance. The type of data in this study is secondary data with a population of all manufacturing sector consumer good industry companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique used purposive sampling in which 26 companies were selected with 4 years of research so that there were 104 observational data. Statistical testing in this study used multiple linear regression analysis. The results of the study concluded that financial distress has a negative and significant effect on tax avoidance. The size of the board of commissioners has a positive and insignificant effect on tax avoidance. Institutional share ownership has a negative and significant effect on tax avoidance. Accounting conservatism has a negative and insignificant effect on tax avoidance. The variables of financial distress, board size, institutional share ownership, and accounting conservatism have a simultaneous effect on tax avoidance.